Highly thin film with aerosol-deposited perovskite quantum dot/metal oxide composite for perfect color conversion and luminance enhancement - Kim, Sunghoon; Kang, Seokwoo; Baek, Seungmin; Song, Jinouk; Mun, Na Eun; Kwon, Hyukmin; Kwon, Hyo Geun; Pu, Yong Jin; Lee, Tae Woo; Yoo, Seunghyup; Oh, Jong Min; Park, Jongwook; et al. (Chemical Engineering Journal, 2022)
Erstwhile, displays using down-converting color changing medium utilized color filters as an essential part of clarifying the trade-off between true colors and transmittance. In this study, we report the development of a novel, smart process for producing thin luminescent films that completely convert colors and enhance light intensity. Highly dense films are prepared by the co-deposition of perovskite quantum dots and metal oxide particles as color conversion layers and scattering agents, respectively. These layers can be directly deposited on blue organic light-emitting diodes using ultrasonic-assisted aerosol deposition (UAD). This method can allow displays using a down-conversion system to streamline the process due to absence of color filters. Using this method, films can be a minimum of 3 µm thick for complete conversion of blue light, a quarter that of inkjet-printed films. We demonstrate 7,353 cd m-2 in green and 411 cd m-2 in red converted emissions with no blue light leakage. Furthermore, the developed technique was shown to be compatible with versatile patterning processes. For example, UAD may be combined with a fine-metal shadow mask to produce a pattern of 30-μm-diameter dots. Even without using a mask, the method still produces a pattern of 13 μm wide lines. This system provides a new approach that may serve as an alternative to inkjet printing.
Keywords: Aerosol deposition; Blue light; Color changing; Color conversions; Color filters; Metal-oxide composites; OLED backlight; Perovskite quantum dot; Scattering effects; Thin-films; Aerosol deposition; Color conversion; OLED backlight; Perovskite quantum dots; Scattering effect